PROFIL TINGKAT KESEGARAN JASMANI SISWA DI SMK TARUNA PEKANBARU - Muliadi BTB, Rido; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the profil of the physicalfitness level of sudents at SMK Taruna Pekanbaru.This reasearch is a quantitativedescriptive study. This reasearch only describes or provides information about asituation. This study uses a test survey with measurements on studen, all student studiedwere measured by an Indonesian physical fitness test. The population and sample of thisstudy were 21 students of SMK Taruna Pekanbaru.instrumen in this study are: 60 meterrun test, 60 second hanging test, 60 second sit-down test, upright jumping test and 1200meter run test. The data taken from this study is directly taken an obtained frompredetermined samples. Based on the result of research and data processing usingphysical fitness test norms and descriptive percentage formula, the obtained the profiledata of the physical fitness level of the student of SMK Taruna Pekanbaru is not in thevery good category, in the good category 2 students with a percentage of 9,52%, in themedium category 8 students with a percentage of 38,09%, in the poor category 11students with a percentage of 53,38%, and in the category of lack there is absolutelynone. So if the average level of physical fitness of students at SMK Taruna Pekanbaru isin the poor kategory.Key Words: Level Of Physical Fitness